'Start to finish trans‐institutional transdisciplinary care': a novel approach improves colorectal surgical results in frail elderly patients. (January 2016) - Chia, C. L. K.; Mantoo, S. K.; Tan, K. Y.
Abstract: Aim: The frail elderly surgical patient is at increased risk of morbidity after major surgery. A transdisciplinary Geriatric Surgery Service (GSS) has been shown to produce consistently positive results in our institution. A trans‐institutional transdisciplinary Start to Finish (STF) programme was initiated incorporating seamless prehabilitation and rehabilitation to enhance the outcome further. Method: Patients who underwent major colorectal resection in Khoo Teck Puat Hospital and were managed under the GSS from January 2007 to December 2014 were included in this prospective study. The STF programme was initiated from January 2012. The surgical outcome of patients managed under the GSS before the initiation of STF was compared with that after its implementation. Results: There were 57 patients after the initiation of the STF programme compared with 60 patients managed before STF. There were 26.4% and 25% of frail patients in the STF group compared with the non‐STF group ( P = 0.874). The mean length of hospital stay was significantly shorter in the STF group (8.4 days vs 11.0 days, P = 0.029). Functional recovery in patients available for follow‐up at 6 weeks showed 100% (46/46) recovery in the elective STF group who received prehabilitation and 95.7% (45/47) in the elective non‐STF group who did not ( P = 0.157). There were no significant differences in a Clavien–Dindo complication score of Grade 3 or more and 30‐day mortality between the two groups. Conclusion: Through a trans‐institutional transdisciplinary approach, we managed to achieve a significantly shorter hospital stay in frail patients having colorectal surgery. All elective patients who received prehabilitation achieved full functional recovery.